The temporal and spatial variation of relative humidity in Iraq - Rajaa Abdullah Basheer Habash (College of Education for Pure Sciences, 2013)
Abstract This research includes the study of the temporal variation and spatial of relative humidity in several locations in Iraq (Mosul, Kirkuk, Baghdad, Rutba and Basra)at these locations the humidity data base was analyzed and studied to find out its relation with different climatic elements. the results indicated the existence of strong linear, proportional and inverse link relations between the relative humidity and different climatic elements. Correlation coefficient values where in the region (0.83-0.99)except the relation with the wind speed where (R) is between (-0.38 to -0.77) The maximum relative humidity values, in winter and spring was in Mosul station. There was a rapid fall in relative humidity values in Summer at all other stations. where the range of the relative humidity values was (%23-%28). The relative humidity values in autumn was close to that taken at spring time for all stations. monthly basis of the time series of relative humidity was analyzed at all stations and it showed that the general direction increase slowly with time (in months) at Rutba and Kirkuk stations, while it decrease with time (in months) at Mosul, Baghdad and Basra Stations.